(untitled) (Research, Society and Development, 2020)
This article proposes a theoretical-reflective study about the way in which social thinking in health was built based on the principles of popular education. We sought to understand how the dissemination of popular education knowledge has contributed to the empowerment of grassroots in their struggle for a role in health care. To support the study, we based mainly on the works of Brandão (2001, 2002), Cruz (2020) and Vasconcelos (2001). Methodologically, the study falls within the scope of qualitative and bibliographic research. The various theoretical productions about Popular Education in Health implemented in Brazil were analyzed. From the analysis, it was clear that popular education played an important role in the construction of social thinking in health, with repercussions on the valorization of the knowledge collectively constructed. The Popular Education in Health, taking as a starting point the enhancement of previous knowledge in the shared construction of knowledge, provides an approximation between members of grassroots movements, people benefited by the health system and its professionals in order to achieve improved rates in health care.